Private ex-ante transaction costs for repeated biodiversity conservation auctions: A case study - Markus Groth (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
The European Union's Council Regulation (EC) No 1698/2005 on support for rural development by the European Agricultural Fund for Rural Development has introduced promising changes in rewarding farmers by the implementation of conservation auctions and granting farmers' transaction costs. The paper therefore deals with the evaluation of private transaction costs within a case study using repeated auctions to reward plant biodiversity. Based on a review of the current literature the paper develops a specific definition of transaction costs as well as a methodology to measure and calculate the farmers' private transaction costs.
Keywords: C93; D44; D82; H41; L14; Q24; Q28; Q57; R52; 330; Agri-environmental policy; biodiversity conservation auctions; transaction costs; ecological services; plant biodiversity; experimental economics; EAFRD-regulation; Biodiversität; Landwirtschaft; Naturschutz; Transaktionskosten; Agrarsubvention; EU-Agrarpolitik; Auktion; EU-Staaten